Pengakuan UNESCO Atas Batik Sebagai Warisan Budaya Tak Benda (WBTB) - Ypriliansi Nora Evita; Agus Trihartono; Adhiningsih Prabhawati (Majalah Ilmiah DIAN ILMU, 2022)
This paper describes how the Indonesian government's efforts to make batik recognized as an Intangible Cultural Heritage by UNESCO. Through qualitative descriptive research with secondary data sources through literature studies, the research shows that efforts to promote batik abroad have been carried out since the era of President Soeharto's administration until now. However, batik promotion efforts are still dominated by the government. Only after there was a claim for batik by Malaysia, non-government elements also participated in promoting batik as a cultural product belonging to Indonesia. The promotion of batik by the government and non-government elements led to batik being recognized as an Intangible Cultural Heritage (WBTB) by UNESCO in 2009.